Lifestyle and fertility: the influence of stress and quality of life on female fertility - Stefano Palomba; Jessica Daolio; Sara Romeo; Francesco Antonino Battaglia; Roberto Marci; Giovanni Battista La Sala (BMC, 2018)
Abstract There is growing evidence that lifestyle choices account for the overall quality of health and life (QoL) reflecting many potential lifestyle risks widely associated with alterations of the reproductive function up to the infertility. This review aims to summarize in a critical fashion the current knowledge about the potential effects of stress and QoL on female reproductive function. A specific literature search up to August 2017 was performed in IBSS, SocINDEX, Institute for Scientific Information, PubMed, Web of Science and Google Scholar. Current review highlights a close relationship in women between stress, QoL and reproductive function, that this association is more likely reported in infertile rather than fertile women, and that a vicious circle makes them to have supported each other. However, a precise cause-effect relationship is still difficult to demonstrate due to conflicting results and the lack of objective measures/instruments of evaluation.